The Perceptions of Preservice Teachers on Culturally Responsive Teaching Through the Lens of Geneva Gay Framework - Cutley, Passion L; Okojie, Felix A. (Advances in Social Sciences Research Journal, 2025)
This study aimed to understand preservice teachers’ perceptions of culturally responsive teaching within a teacher preparation program, guided by Geneva Gay’s Culturally Responsive Teaching Framework. The research questions examined the extent of preservice teachers’ knowledge of cultural diversity, their ability to validate the cultural identities of diverse learners, and their implementation of culturally responsive teaching practices. Utilizing a qualitative methodology, the study allowed participants to express their views on their preparedness to be culturally responsive teachers based on their training. The study population consisted of full-time college students enrolled in a teacher preparation program, all of whom had some fieldwork experience. The findings indicated that teachers should establish culturally responsive learning environments that are inclusive and safe, which includes being aware of their biases and being culturally sensitive to diverse learners. Additionally, the study highlighted the need for teacher preparation programs to offer more inclusive teaching strategies and resources to ensure cultural sustainability as preservice teachers begin working with diverse student populations.